Wagner : histoire d'un artiste - Pourtalès, Guy de 1881-1941 (Paris Gallimard, 1932)
‘Wagner: Story of an Artist’ is a biography of Richard Wagner written by the Swiss writer Guy de Pourtalès. The book was first published in 1900. It is a detailed exploration of the life and work of the celebrated German composer Richard Wagner, one of the most influential figures in nineteenth-century opera. In this book, Guy de Pourtalès examines Wagner's personal and artistic life, looking at his career as a composer, his musical works, his relationship with other artists and intellectuals of the time, and the social and political circumstances that influenced his work. The book also offers an insight into de Pourtalès's views on Wagner's impact on the music and culture of his time. Guy de Pourtalès's approach to this biography is often seen as subjective and literary, with a particular focus on the aesthetic and emotional aspects of Wagner's life. (Translated with Deepl.com)
Keywords: Wagner, Richard -- 1813-1883; Music history; Biography; Composer; Opera